An Unusual Case of Noncatamenial Recurrent Pneumothorax - Kirschbaum, Andreas; Greulich, Timm; Mirow, Nikolas; Bartsch, Detlef K. (The Thoracic and Cardiovascular Surgeon Reports, 2018)
In a 28-year-old female, seven recurrent pneumothoraces occurred during a period of 2 years despite multiple thoracic interventions, all on the left thoracic side. Despite profound differential diagnostic analysis, the underlying cause remains unclear. An accumulation of conditions in this patient affecting only the left half of the body is remarkable: sinistral glaucoma as an infant, a sinistral pigmentation disorder, and a sinistral Bochdalek hernia.
Keywords: thoracic surgery; lung; benign or congenital lesions; pneumothorax